Birefringence and Dichroism in Quasi‐1D Transition Metal Trichalcogenides: Direct Experimental Investigation. Issue 21 (22nd April 2021) - Hou, Shijun; Guo, Zhengfeng; Yang, Juehan; Liu, Yue‐Yang; Shen, Wanfu; Hu, Chunguang; Liu, Shiyuan; Gu, Honggang; Wei, Zhongming
Abstract: Birefringence and dichroism are very important properties in optical anisotropy. Understanding the intrinsic birefringence and dichroism of a material can provide great help to utilize its optical anisotropy. But the direct experimental investigation of birefringence in nanoscale materials is rarely reported. As typical anisotropic transition metals trichalcogenides (TMTCs) materials with quasi‐1D structure, TiS3 and ZrS3 have attracted extensive attention due to their special crystal structure and optical anisotropy characteristics. Here, the optical anisotropy properties such as birefringence and dichroism of two kinds of quasi‐1D TMTCs, TiS3 and ZrS3, are theoretically and experimentally studied. In experimental results, the anisotropic refraction and anisotropic reflection of TiS3 and ZrS3 are studied by polarization‐resolved optical microscopy and azimuth‐dependent reflectance difference microscopy, respectively. In addition, the birefringence and dichroism of ZrS3 nanoribbon in experiment are directly measured by spectrometric ellipsometry measurements, and a reasonable result is obtained. This work provides the basic optical anisotropy information of TiS3 and ZrS3 . It lays a foundation for the further study of the optical anisotropy of these two materials and provides a feasible method for the study of birefringence and dichroism of other nanomaterials in the future. Abstract : Optical anisotropy of quasi‐1D transition metals trichalcogenides of TiS3 and ZrS3 including anisotropic refraction, anisotropic reflection, birefringence, and dichroism are systematically investigated in experimental setup. Anisotropic refraction of TiS3 and ZrS3 nanoribbons are expressed by polarization‐resolved optical microscopy, and anisotropic reflection are expressed by azimuth‐dependent reflectance difference microscopy. Birefringence and dichroism of ZrS3 are measured by Mueller matrix spectrometric ellipsometry.